Impact of Incorporating NIR Reflective Pigments in Finishing Coatings of ETICS - Nuno Ramos (2021)
Near-infrared (NIR) reflective materials are being developed for mitigating building cooling needs. Their use contributes to broadening the range of colours, responding to the urban aesthetic demand without compromising the building performance. Despite the increase in NIR reflective pigments investigation, there is still a knowledge gap in their applicability, impact, and durability in multilayer finishing coatings of External Thermal Insulation Composite Systems (ETICS). Hence, the main goal of this work consists of evaluating the impact of incorporating NIR reflective pigments (NRP) in the solar reflectance of the surface layer of ETICS, without affecting the colour perception, as well as their influence on the colour durability and surface temperature. As such, colour, solar reflectance, and surface temperature were monitored for 2 years in dark-coloured specimens of ETICS, with and without NRP and a primer layer. It was confirmed that the main contribution of NRP is the increase of solar reflectance and, consequently, the decrease in surface temperature, especially for high exterior temperatures (around 30 degrees C). Moreover, these pigments highly increase the NIR reflectance without affecting the visible colour. In addition, they contribute to maintaining the colour characteristics. The application of primer increased the surface temperature, especially for higher exterior temperatures. However, it contributes to a lower colour difference and solar reflectance variation, which is an important achievement for durability purposes.